Great christian jurists in French history - Descamps, Olivier; Domingo, Rafael (Cambridge University Press, 2019)
Ivo de Chartres (Yves de Chartres) / Christof Rolker -- Stephen of Tournai (Étienne de Tournai) / Kenneth Pennington -- Guillaume Durand / Orazio Condorelli -- Jacques de Revigny / Paul J. du Plessis -- Pierre de Belleperche / Yves Mausen -- Charles Dumoulin / Wim Decock -- John Calvin (Jean Calvin) / John Witte, Jr -- Jacques Cujas / Xavier Prévost -- Francois Hotman / Mathias Schmoeckel -- Hugues Doneau / Christian Hattenhauer -- Jean Bodin / Daniel Lee -- Jean Domat / David Gilles -- Henri François d'Aguesseau / Isabelle Brancourt -- Robert-Joseph Pothier / Olivier Descamps -- Jean-Étienne-Marie Portalis / Nicolas Laurent-Bonne -- Alexis de Tocqueville / Mary Ann Glendon -- Paul Viollet / Anne-Sophie Chambost -- Paul Fournier / Brigitte Basdevant-Gaudemet and Rafael Domingo -- Raymond Saleilles / Marco Sabbioneti -- Maurice Hauriou / Julien Barroche -- Léon Duguit / M. C. Mirow -- Georges Ripert / Frédéric Audren -- Jacques Maritain / William Sweet -- Robert Schuman / Rafael Domingo -- Gabriel le Bras / Kathleen G. Cushing -- Jean Carbonnier / Laetitia Guerlain -- Michel Villey / Luisa Brunori.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Geschichte; Glaube; Jurist; Frankreich; Christentum